2014
DOI: 10.5114/pg.2014.47897
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between social factors and anxiety-depression in function dyspepsia: do relationships exist?

Abstract: IntroductionFunction dyspepsia (FD) may cause patients to suffer from anxiety and depression, and psychosocial disorders would have a significant effect on FD symptoms.AimTo examine the prevalence of anxiety and depression among function dyspepsia (FD) patients and to identify social factors of anxiety-depression among FD patients.Material and methodsPatients with FD, who fulfilled the Rome III criteria, were enrolled. All patients were administered a validated Chinese version of the self-rating scale (SDS) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 31 publications
1
19
0
1
Order By: Relevance
“…In the present single-centre young adult study population, the prevalence of FD was found to be 34.69%, which is within the range reported by previously published studies. 4 , 20 …”
Section: Discussionmentioning
confidence: 99%
“…In the present single-centre young adult study population, the prevalence of FD was found to be 34.69%, which is within the range reported by previously published studies. 4 , 20 …”
Section: Discussionmentioning
confidence: 99%
“…Huang et al enrolled 907 patients with functional dyspepsia that fulfilled the Rome III criteria and validated them using the Chinese version of the self-rating scale and self-rating anxiety scale [23]. Five hundred and sixteen of the sample have functional dyspepsia and anxiety-depression status.…”
Section: Reviewmentioning
confidence: 99%
“…These results are in accordance with results from other studies. Huang et al 17 study results show that anxiety and depression are more severe in FD patients, and that female gender, older age and lower education levels are all risk factors for both anxiety and depression. A Swedish population-based study determined a positive correlation between anxiety and FD but failed to prove a correlation between depression and FD 18 .…”
Section: Discussionmentioning
confidence: 94%